ROLE OF REDUCING CELL LEAKAGE IN CELL CULTURE USING LARGE PORE SIZE PERMEABLE MEMBRANE - Nur Kaliwantoro; Marsetyawan HNE Soesatyo; Indarto Indarto; Mohammad Juffrie; Rini Dharmastiti; Suprihatin Suprihatin (Universitas Gadjah Mada, 2016)
Permeable membranes are widely used in many in vitro studies using cell culture. Some cell leakage are often occurs when using permeable membrane with large pore size. Unfortunately the use of permeable membrane with smaller pore size in permeability studies faces some difficulties due to its small pore size and pore density. Recent study provides the protocol in using permeable membrane with large pore size with smaller cell leakage. Vero cell line (CCL-81, ATCC) was used and culture on polyester permeable membrane with 3 µm pore size. Visualization using inverted microscope was used to analized the cell leakage on the permeable membrane. Parallel plate flow chamber was used to analized the permeability performance of the Vero cell cultured on the permeable membrane. The result showed that the current technique is significant in reducing cell leakage of the cell cultured on large pore size of permeable membrane. The same results were found in using polyester and polycarbonate permeable membrane.